The Longevity of Aedes aegypti Larvae in Several Water Sources in Surabaya - Antonio Ayrton Widiastara; Gabriel Pedro Mudjianto; Etik Ainun Rohmah; Hengki Anggara Putra; Martha Indah Widia Ningtyas; Sri Wijayanti Sulistyawati; Suhintam Pusarawati; Fitriah; Kasiyama Desi Indriyani; Alpha Fardah Athiyyah; Basuki, Sukmawati (Institute of Topical Disease Universitas Airlangga, 2022)
Aedes aegypti transmits the dengue virus that causes Dengue Viring the high number of DVI cases is the existing breeding places of Ae. aegypti. The water sources used by the community and the surrounding environment are essential media for living Ae. aegypti larvae. This recent study aimed to detect the longevity of Ae. aegypti larvae in diï¬€ erent water sources in Surabaya and the killing eï¬€ect of temephos. An analytical observational and experimental study was conducted in August-September 2021. Twenty-instar III Ae. aegypti larvae were put in each 100 ml beaker glass containing diï¬€ erent water sources, such as rain, well, mineral, new and used bath water, and antiseptic soapy water. Fungi in water sources were examined. Two groups were set with and without temephos, the ï¬nal temephos concentration was of 0.00001 ppm. Live Ae. aegypti larvae, pupae, mosquitoes were observed every 24 hours for seven days without feeding. Living larvae were still found on Day 7 in all water sources with and without temephos. There were more larvae live in soapy water without temephos, particularly on Day 2 to Day 6, compared to other water sources either without or with temephos. In contrast, many larvae died in mineral water with temephos. Some larvae turned into pupae, started on Day 1. Pupae and mosquitoes were mostly found in rain water with temephos. Ae. aegypti larvae survived better in soapy water either with or without temephos. Temephos seemed to be eï¬€ective to kill Ae. aegypti larvae in mineral water, and might induce larvae in turning to pupae and mosquitoes quickly at low concentration.